2023
DOI: 10.37496/rbz5220210199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactic acid bacteria preparations on calf fecal flora

Abstract: This experiment was conducted to investigate the effects of lactic acid bacteria preparations on microbial diversity and community structure of calves. On days 1 and 7 of the trial period, feces were collected into sterile tubes and labeled (Day 1: control group D1DZ, experimental group D1SY, and Day 7: control group D7DZ, experimental group D7SY). Twenty Angus calves (150±10 kg) were selected and randomly divided into two groups of 10 calves each. The control group fed a basal diet. In addition to feeding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…The current results suggest that probiotic supplementation regulates the bacterial community composition in the intestine of calves, particularly in 6BY + 6BZ-supplemented calves (mainly in terms of diversity at the genus level) that may promote the absorption of nutrients in diets [ 37 ]. It has been reported that feeding lactic acid bacteria preparations for one day affects the microbial species composition of the feces of calves through β diversity data analysis using multivariate statistical tools such as principal component analysis [ 64 ]. Additionally, Fan et al [ 65 ] reported that the β diversity of fecal microbiota of Holstein dairy calves was influenced by the supplementation with milk replaced with ethoxyquin, improving early rumen microbial development; this suggests that the interactions among different bacteria genera might play an essential role in maintaining intestinal homeostasis in the gut of newborn calves; moreover, the major impact on microbiota composition and diversity is directly related to the combined probiotic supplementation [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current results suggest that probiotic supplementation regulates the bacterial community composition in the intestine of calves, particularly in 6BY + 6BZ-supplemented calves (mainly in terms of diversity at the genus level) that may promote the absorption of nutrients in diets [ 37 ]. It has been reported that feeding lactic acid bacteria preparations for one day affects the microbial species composition of the feces of calves through β diversity data analysis using multivariate statistical tools such as principal component analysis [ 64 ]. Additionally, Fan et al [ 65 ] reported that the β diversity of fecal microbiota of Holstein dairy calves was influenced by the supplementation with milk replaced with ethoxyquin, improving early rumen microbial development; this suggests that the interactions among different bacteria genera might play an essential role in maintaining intestinal homeostasis in the gut of newborn calves; moreover, the major impact on microbiota composition and diversity is directly related to the combined probiotic supplementation [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to results from previous studies on cow rumen fluid, Prevotellaceae and Fibrobacter can be found at frequencies of around 28% and 12%, respectively [30,31,37,45]. However, in ruminant fecal samples, Prevotellaceae and Fibrobacter are usually present in a rather low abundance, reaching between 0.4% and 1.4% [22,35,40,46]. Furthermore, with a similar function to Fibrobacter, members of Atopostipes are hydrolytic bacteria which promote the hydrolysis of cellulose and lignin contents to produce simple sugars [47,48].…”
Section: Bacteria Community Structurementioning
confidence: 99%
“…According to Wang (2023) and Liu (2022), who compared the rumen microbial communities between Yaks and Qaidam cattle, the relative abundance of the Rikenellaceae_RC9_gut_group and the Christensenellaceae_R-7_group in Yaks was revealed to be higher, reaching 10.6% and 8.0%, respectively [39]. On the other hand, Dong (2023) found a lower abundance of the Rikenellaceae_RC9_gut_group (7.06%) and the Christensenellaceae_R-7_group (5.27%) when studying cow fecal flora [40]. In the same line of study, Mutungwazi (2022) compared four animal manures which are routinely used as inoculum in anaerobic digestion and revealed a lower abundance of the Christensenellaceae_R-7_group for pig (1.4%), horse (0.4%), chicken (0.2%), and cow (4.6%), and no significant presence of the Rikenellaceae_RC9_gut_group [17].…”
Section: Bacteria Community Structurementioning
confidence: 99%